BEBERAPA KARAKTER MORFOLOGIS TANAMAN SALAK (Salacca zalacca (Gaert) Voss) DI KAMPUNG BAWOLEU, KECAMATAN TAGULANDANG UTARA, KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO - Pulakiang, Andrew R.; Polii-Mandang, Jeany Sh.; Sompotan, Saartje (EUGENIA, 2017)
ABSTRACTÂ The objective of this research was toÂ  know the whether thete is a difference the nature of morphological characters local bark and bark butter who grewup in the slums Bawoleu, Tagulandang subdistrict north, Districts of the Siau Tagulandang Biaro Archipelago. This research has been conducted the Village Bawoleu, Tagulandang subdistrict north, Archipelagic Districts Siau Tagulandang Biaro. Research activities implemented starting in November 2016 until Januari 2017. Research conducted using the survey method by means of sampling selected that is Village Bawoleu which is a central plant snake fruit. Samples were taken from the Village Bawoleu and have determined the yard barking plant, many samples of local plants and snake fruit butter set 20 plants were taken by purposive sample, of each plant sample was taken mother longest petiole and fifteenth child leaves. In addition to any plant samples were taken of the bunches and each taken four bunches of fruits to be observed. Based on research results from some plants morphological characters barking in the the Village Bawoleu there are similarities and some differences in morphological characters.Keywords : bark fruit, morphological characters, Tagulandang